The mystery of spectral breaks: Lyman continuum absorption by photon-photon pair production in the Fermi GeV spectra of bright blazars - Boris E. Stern; Juri Poutanen (IOP PUBLISHING LTD, 2022)
We re-analyze Fermi/LAT γ -ray spectra of bright blazars using the new Pass 7 version of the detector response files and detect breaks at ∼5 GeV in the rest-frame spectra of 3C 454.3 and possibly also 4C +21.35, associated with the photon–photon pair production absorption by the He ii Lyman continuum (LyC). We also detect significant breaks at ∼20 GeV associated with hydrogen LyC in both the individual spectra and the stacked redshift-corrected spectrum of several bright blazars. The detected breaks in the stacked spectra univocally prove that they are associated with atomic ultraviolet emission features of the quasar broad-line region (BLR). The dominance of the absorption by the hydrogen Ly complex over He ii, a small detected optical depth, and break energy consistent with head-on collisions with LyC photons imply that the γ -ray emission site is located within the BLR, but most of the BLR emission comes from a flat disk-like structure producing little opacity. Alternatively, the LyC emission region size might be larger than the BLR size measured from reverberation mapping, and/or the γ -ray emitting region is extended. These solutions would resolve the long-standing issue of how the multi-hundred GeV photons can escape from the emission zone without being absorbed by softer photons.